Halal Certification Process by Local Governments and Muslim Organizations in Australia - Humaira Naznii (Journal of International Islamic Business Studies, 2024)
The research article will discuss the halal certification process and the cooperation of Muslim organizations in Australia with local governments. in Australia. A halal certificate is a legal document issued by the government that certifies that the meat was produced in accordance with Islamic law. Australia is the world's largest meat-producing country. This makes Australia must meet the demand of producers. With the export of meat consumed by Muslim countries, Australia must have halal certification for its consumer products, this is due to requests submitted by Muslim countries themselves. Halal certification is a hot topic of discussion. especially issues of funding a product to receive halal certification. The price of acquiring a halal certification varies greatly depending on the product, the organization, the location of the certification office, and whether the food will be exported or will only be consumed domestically.